2005
DOI: 10.1002/jsfa.2392
|View full text |Cite
|
Sign up to set email alerts
|

Application of agglomerative hierarchical clustering to identify consumer tomato preferences: influence of physicochemical and sensory characteristics on consumer response

Abstract: A multiple regression model was developed to predict the acceptability of the four tomato varieties studied (Aranka, Cherry, Beef and Pitenza). Agglomerative hierarchical clustering showed the presence of four consumer clusters. One cluster preferred small tomatoes (Aranka and Cherry) and another cluster the larger tomatoes (Beef and Pitenza). In the sensorial analysis Aranka was the preferred variety, scoring more highly in taste, odour, acidity, sweetness and hardness. In the physicochemical analysis Aranka … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 17 publications
4
24
0
1
Order By: Relevance
“…The ratio between soluble solids and percent titratable acidity is used widely as it is considered a better sensory indicator than either soluble solids or acidity alone. The SS/TA has been reported correlated with overall liking of tomato consumers (Baldwin and others ; Serroano‐Megias and Lopez‐Nicolas ). These findings have also been demonstrated in research with other fruits such as table grapes (Jayasena and Cameron ).…”
Section: Resultsmentioning
confidence: 93%
“…The ratio between soluble solids and percent titratable acidity is used widely as it is considered a better sensory indicator than either soluble solids or acidity alone. The SS/TA has been reported correlated with overall liking of tomato consumers (Baldwin and others ; Serroano‐Megias and Lopez‐Nicolas ). These findings have also been demonstrated in research with other fruits such as table grapes (Jayasena and Cameron ).…”
Section: Resultsmentioning
confidence: 93%
“…The texture of fleshy fruits is a key quality criterion that determines uses and consumer preference [1][2][3][4]. More effective control of fruit texture is a major objective for the fruit production, transformation, and retail sectors [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Conducted sensory evaluation indicated that there were slightly expressed some differences in sensory attributes observed by panelists between two different cultivars and two types of cultivation, but they did not show significant differences in any sensory attribute when dealing with two different strawberry cultivars or two types of cultivation (Bursac et al 2007). Another critical component for consumer's perception of tomato fruit quality is texture (Causse et al 2002, Serrano-Megias andLopez-Nicolas 2006). Another critical component for consumer's perception of tomato fruit quality is texture (Causse et al 2002, Serrano-Megias andLopez-Nicolas 2006).…”
Section: Factors Affecting Flavor and Sensory Quality Of Fruitsmentioning
confidence: 99%